EFEKTIVITAS MODEL BLENDED PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR - Anwar Wahid; Muhammad Yahya; Anas Arfandi (UNM Journal of Technology and Vocational, 2023)
This study aims to: (1) knowing the blended problem based learning model based on Moodle LMS which is effective in increasing student motivation, and (2) knowing the differences in learning motivation who take part in the study blended problem based learning model based on Moodle LMS with students following the blended learning model. The research design used is quasi-experimental. The population in this study was the second semester students of the class of 2021 who studied introductory accounting courses in the accounting department with a total of 140 people. The sample of this research is class A as many as 34 people as the experimental class and class D as many as 33 people as the control class. The sampling technique used purposive sampling technique. The results showed that: (1) The implementation of the blended problem based learning model based on the Moodle LMS was effective on the learning motivation of the students of the Accounting Department, the Faculty of Economics and Islamic Business, Alauddin Islamic State University (2) The results of the inferential analysis using the paired simple t test show that the t-count value is greater than the t table with a sig value less than 0.05, which means that the implementation of the blended problem-based model Moodle-based LMS learning effectively increases student motivation and (3) The results of the inferential analysis with the independent simple t test show that the t-count value is greater than the t-table with a sig value less than 0.05 which means that learning motivation of experimental class students has a significant difference with learning motivation of control class students.